Synthesis and Characterization of Polylactide-Poly(ethylene glycol) Block Copolymer as Solid Polymer Electrolyte - Tan, C.H.; Ahmad, A.; Anuar*, F.H. (Asian Journal of Chemistry, 2014)
A solid polymer electrolyte was developed from polylactide-poly(ethylene glycol) (PDLLA-PEG) block copolymer with lithium iodide as conducting salt. At the initial stage, the polymer host was synthesized by ring opening polymerization of DL-lactide followed by chain extension reaction using hexamethylene diisocyanate (HMDI). The poly(ether-ester-urethane) electrolyte thin films (13-18 mm) with various lithium iodide load were then prepared by solution casting technique. The formation of ester bond and urethane linkage in PDLLA-PEG-PDLLA triblock and multiblock copolymers, respectively, were confirmed using NMR spectrometer. Chemical interaction between polymer host and lithium cation from lithium iodide was confirmed by ATR-FTIR technique by observing the shift of wavenumber for the carbonyl (C=O) (1770-1730 cm-1) and ether (C-O-C) (1160-1040 cm-1) groups. Structural analysis carried out by XRD showed that crystallinity of the poly(ethylene glycol) soft block was reduced and became fully amorphous as the amount of lithium iodide increased up to 20 wt. %. Thermal studies by TGA indicated that poly(ester-ether-urethane) electrolyte was thermally stable up to 200 °C while DSC revealed the relation between electrolyte thermal properties and the lithium iodide content. The resulted solid polymer electrolyte with 25 wt. % lithium iodide load was found to achieve optimum ionic conductivity of 4.1670 × 10-6 S cm-1 at room temperature as compared to pure polymer host conductivity of 4.423 × 10-11 S cm-1, which denoted an increment of five magnitudes in ionic conductivity.